Analisis Kesiapsiagaan Masyarakat dalam Menghadapi Bencana di Desa Cikunir, Tasikmalaya, Jawa Barat 2023 - Rifki Wiratama (Universitas Widya Gama Mahakam Samarinda, 2024)
Disaster is an event or series of events that threaten and disrupt the lives and livelihoods of communities, caused by natural and/or non-natural factors as well as human factors, resulting in loss of human lives, environmental damage, property loss, and psychological impact. The aim of this research is to assess the readiness of the community in Cikunir Village, Tasikmalaya Regency, regarding disasters. This research uses a descriptive method with a quantitative approach. The findings conclude that the community in Cikunir Village is not prepared for the possibility of various disasters, whether natural or non-natural. Therefore, efforts should be made to enhance community preparedness. Recommendations for this research include increasing public awareness through more intensive educational campaigns, addressing various types of disasters, early warning signs, and potential impacts. Local government should ensure the availability of information through various channels, involve community leaders, and develop effective outreach strategies. Keywords: Preparedness, disaster, vulnerability